Lymph node status after resection for gallbladder adenocarcinoma: Prognostic implications of different nodal staging/scoring systems. Issue 3 (13th October 2014) - Amini, Neda; Spolverato, Gaya; Kim, Yuhree; Gupta, Rohan; Margonis, Georgios Antonios; Ejaz, Aslam; Pawlik, Timothy M.
<x xml:space="preserve">Abstract</x> Background and Objectives Several lymph node (LN) staging/scoring systems have been proposed to stratify the prognosis of patients with gallbladder adenocarcinoma (GBA). We sought to define the prognostic performance of the most commonly utilized LN staging/scoring systems including AJCC/UICC N stage, lymph node ratio (LNR), log odds (LODDS), and N score, among patients with GBA. Method Between 2004 and 2010, 1, 124 patients with GBA were identified from the Surveillance Epidemiology and End Results (SEER) database. The discriminative ability of each LN staging/scoring system was assessed using the Akaike's Information Criterion (AIC) and the Harrell's concordance index. Results When assessed using categorical values, LNR had a modest, improved ability to discriminate patients with regard to prognosis (C‐index: 0.615; AIC: 2118.2) compared with AJCC/UICC N stage or N score and a prognostic discrimination comparable to LODDS. Among patients who had a total number of LN examined (TNLE) of 1 or 2, all the staging/scoring systems performed comparably. In contrast, among patients who had ≥4 TNLE, LODDS performed the best (C‐index: 0.613; AIC: 303.2). Conclusion The performance of the different LN staging/scoring systems varied based on the TNLE. In particular, for patients who had ≥4 TNLE, LODDS out‐performed the other staging/scoring systems. J. Surg. Oncol. 2015 111:299–305. © 2014 Wiley Periodicals, Inc.